2018
DOI: 10.1590/1807-3107bor-2018.vol32.0064
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary sinus floor pneumatization and alveolar ridge resorption after tooth loss: a cross-sectional study

Abstract: This is a cross-sectional study that aimed to estimate maxillary sinus floor (MSF) pneumatization in single missing tooth of posterior maxilla, by using cone-beam computed tomography (CBCT). CBCT images were analyzed bilaterally and divided into 2 groups: edentulous site (EdS) -edentulous single region of upper second premolar, first or second molars; Tooth site (TS) -contralateral region homologous to the EdS region, with tooth present. Variables evaluated were: sinus height (SH), estimated sinus pneumatizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 17 publications
(13 reference statements)
1
53
0
6
Order By: Relevance
“…It was reported that sinus pneumatization was larger following extraction of teeth surrounded by a superiorly curving sinus floor. A recent cross‐sectional study using CBCT demonstrated sinus pneumatization predominantly occurred at extraction sites where the sinus floor was located more apical than the root apex, and hardly occurred at the sites located coronal than the root apex (Cavalcanti et al, ). However, in the present study, no correlation was found between the extent of sinus pneumatization and the anatomy of the sinus floor.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that sinus pneumatization was larger following extraction of teeth surrounded by a superiorly curving sinus floor. A recent cross‐sectional study using CBCT demonstrated sinus pneumatization predominantly occurred at extraction sites where the sinus floor was located more apical than the root apex, and hardly occurred at the sites located coronal than the root apex (Cavalcanti et al, ). However, in the present study, no correlation was found between the extent of sinus pneumatization and the anatomy of the sinus floor.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, cone-beam computed tomography (CBCT) is a common diagnostic tool that supports threedimensional (3D) imaging and provides thin, detailed sections to assess the relationship between the maxillary sinus floor and the alveolar bone ridge. Although this method reduces the overlapping of anatomical structures and enables a better assessment, a few studies used CBCT to analyze sinus floor pneumatization in the posterior maxilla [1,2,[7][8][9]. The purpose of this study was to determine the amount of sinus pneumatization after the extraction of maxillary teeth in the premolar and molar regions associated with the maxillary sinus via the evaluation of panoramic views.…”
Section: Discussionmentioning
confidence: 99%
“…This thin bone may break and dislocate during extraction, potentially causing the sinus to expand toward the socket. Additionally, larger amounts of pneumatization can occur after molar extraction [1,2,4]. These larger defects can be observed in the alveolar bone after molar extraction, and the longer healing period required allows the sinus to pneumatize.…”
Section: Introductionmentioning
confidence: 99%
“…Tales condiciones generan decisiones particulares de tratamiento, pues en un 54 % de los casos se requieren procedimientos quirúrgicos previos a la colocación de implantes o a la confección de prótesis totales. Adicionalmente, se ha observado que la pérdida de dientes en el maxilar superior se asocia con neumatización sinusal y se necesita cirugía de elevación de seno en más de la mitad de los casos (6).…”
Section: Introductionunclassified